(untitled) (World Bulletin of Management and Law, 2024)
The present scientific article examines issues related to assessing the state of legality and legal culture in the context of protecting individual rights and the development of the legal aid institution in the country. Special attention is given to the importance of providing the population with effective and qualified legal support, enabling citizens to actively and successfully defend their rights and lawful interests. Particular emphasis is placed on the role of the lawyer in criminal proceedings, where they may act on the side of defense or represent the interests of third parties. The authors underscore the invaluable significance of the lawyer’s activities, as they are capable of ensuring justice for both the accused and victims through defense and representation in legal proceedings. The article is grounded in a regulatory framework, including Article 141 of the Constitution of the Republic of Uzbekistan, dedicated to the legal profession. The authors highlight the role of the state as a guarantor of the right of every individual to receive qualified legal assistance, providing lawyers with conditions for unhindered and confidential interaction with their clients.